(3GdCSS GdOSJhQjI h GdbGfhfjI ddJShjI GdbVGFjI ddefGRYGJ GdEOGQjI GdOhdjI ai GdOSJhQ GdYQGbi h GdbGfhf GdOhdi (B/ s - (3SfGf WGdH YHOGdTgjOs; (3CMeO CHhGdhaG s; (3QCaJ ahOIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3Ef ehVhY GdbGfhf GdEOGQi GdOhdi h efGRYGJ gPG GdbGfhf CVMi ef GdehVhYGJ GdJi JMXi HCgejI bUhi(B: (3djS Ydi GdeSJhi GdOhdi aMSH(B: (3Hd Ydi GdeSJhi GdOGNdi cPdc aJhajQ GdYOGdI h GdGWeFfGf GdcGajjf dehXai GdefXeGJ GdOhdjI HGJ GdTZd GdTGZd dcd Phi GdTCf ef GdeYfjjf ShGA OGNd GdefXeGJ GdOhdjI PGJgG(B: (3Ch MJi ChdFc OGNd GdCfXeI GdbGfhfjI GdhWfjI(B: (3HSHH Cf cd ehXa Ohdi jMed LfSjI JQHWg HOhdI eG(B: (3h dG jge Cf Jchf YVhG HGdefXeI Ce de Jcf cPdc(B: (3h hGVM ef YfhGf GdOQGSI Cfg jJYdb HCcKQ ef GNJUGU hGMO ef GNJUGUGJ GdbGfhf(B: (3Ci HCcKQ ef aQY hGMO ef aQhYg(B: (3aGdMOjK Sjchf Yf JShjI bVGFjI defGRYGJ EOGQjI Ydi GdeSJhi GdOhdi(B: (3JMed ef GdUaGJ h GdNUGFU eG jLYdgG JLeY eG Hjf aQYi GdbGfhf GdEOGQi h GdbGfhf GdOhdi(B: (3h djS GdbGfhf GdOSJhQi YfgG HHYjO(B: (3Hd gh hKjb GdUdI HgG(B. (3h gPG GdfhY ef GdehGVjY HGJ ef GdCehQ GdeJOGhdI h GdebHhdI ai YGde GdbGfhf efP hbJ jcGO jchf WhjdG(B: (3h de jYO OGQSi GdbGfhf h TQGMg jSJZQHhf ef GdJUOi dgcPG ehGVjY h ETHGYgG HMKG(B: (3Hd de jYO CMO (B- (3Ed fGOQG (B- (3jSJZQH hLhO gcPG CfhGY ef GdOQGSGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2016s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B602-622s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdCSS GdOSJhQjIs; (3GdOSJhQ GdYQGbi h GdbGfhf GdOhdis; (3GdefGRYGJ GdEOGQjI GdOhdjIs; (3GdJShjI GdbVGFjI s; (3GdOSJhQ GdYQGbj s; (3GdbVGA GdEOGQj GdOhdj s; (3GdeMceI GdEOGQjI dYUHI GdCee s; (3JTcjd GdeMGce GdEOGQjI GdOhdjI s; (3GdJXde GdEOGQj s; (3GdJCOjH GdEOGQjs; (3GdLRGA GdJCOjHj s; (3GdCMcGe GdEOGQjI GdOhdjI s; (3eMceI GdYOd GdOhdjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes